Microbial enhanced oil recovery: interfacial tension and biosurfactant-bacteria growth - Wira Putra; Farizal Hakiki (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract Microbial enhanced oil recovery (MEOR) is a method that utilises bacteria or bioproducts to increase oil recovery at the tertiary stage. Clostridium sp. produces biosurfactant that alters rock–fluid properties and increases oil detachment. The interaction between bacteria and surfactant is interesting relation to study. We revisit and develop models for biosurfactant-producing bacteria’s growth and the interfacial tension (IFT) response. The biosurfactant-producing bacteria growth model (BBG model) mimics the predator–prey interaction and the IFT response model derived from analogy. Both models form an integrated model called coupled-simultaneous model. We deliver the suitability of these models to experimental datasets by conducting parameter estimation. The decreased number of parameter in BBG model is with the help of rate estimation model. It estimates the bacteria growth rate and biosurfactant production rate. This research introduces a graphical method to narrow parameters initial guess in the IFT model. The method comes with a proposed index to compare surfactant performance called as surfactant performance index (SPI). The paper exposes the logic of each parameter, physics behind the models, and addresses the mathematical artefacts. The significant findings are valuable to anticipate bacterial performance for MEOR.